VD_FINDINFO Jug / 2022 / 111 vom 25. März 2021 - VD Tribunal cantonal (2021)
ESCROQUERIE, CONSTATATION DES FAITS, FIXATION DE LA PEINE, ASSISTANCE PUBLIQUE, COMPLICITÉ | 146 CP, 47 CP, 49 al. 1 CP, 10 CPP (CH)